A New Model of Education for the Elderly: Intergenerational Learning - Hou Yongmei (An Overview of Literature, Language and Education Research Vol. 10, 2025)
Background: Intergenerational learning is a combination of lifelong learning and universal learning, which plays a significant role in cultural inheritance, intergenerational understanding, and active aging. Objective: The objective of the study is to understand the concept, role, form, current status, and theoretical basis of intergenerational learning. Methods: Using the keywords "the elder" or "older people" or "old people" and "intergenerational learning", a literature search was conducted in PubMed, Web of Science, CINAHL Plus, Scopus, Embase, PsycINFO, and CNKI for empirical papers published in English or Chinese in the past 20 years. Results: Twenty-six papers were included. Previous literature shows that intergenerational learning among the elderly has increasingly attracted the attention of the academic community. Intergenerational learning can arouse the attention of all sectors of society to elderly education, change the educational concepts of the elderly, increase the learning benefits of both generations, enhance intergenerational understanding and trust, alleviate age discrimination, improve learners’ sense of happiness, and integrate elderly education resources. However, there are still shortcomings in research paradigms and methods, as well as operational models, in intergenerational learning. Conclusion: This article helps to deepen the understanding and attention of all sectors of society to the issue of intergenerational learning among the elderly. In the future, we should integrate social resources, strengthen theoretical research and multidisciplinary collaboration, and improve research paradigms, methods, and operational models of intergenerational learning for the elderly.